Crosslinking kinetics of cation-hydrocolloid gels - Mammarella, Enrique José (2003)
The gel formation of hydrocolloid (sodium alginate and kappa-carrageenan) is the result of the molecule aggregation in presence of an effective cation. The gelling process was considered as a process of diffusion–reaction between the effective cation and the hydrocolloid to produce a porous solid structure. A simple mathematical model for predicting the reaction interface position in alginate or alginate-carrageenan gelation was developed. The model represents appropriately the physicochemical phenomenon and allows to determine the time for complete crosslinking of the hydrocolloid and the amount of incorporated ions.